New Evidence for Asherata/Asherah - Richard S. Hess (Religions)
This paper examines the appearance of published West Semitic spellings of the name of the deity commonly referred to as Asherah. In light of new evidence from the Bronze Age Amorite sources, as well as the complete publication of the inscriptions at Kuntillet ʿAjrud, a review of the analysis and discussion concerning the identification of the deity is undertaken. The purpose will be to ascertain the significance of the witness of epigraphic Hebrew texts at Kuntillet ʿAjrud and Khirbet el-Qom in light of earlier Bronze Age evidence, the biblical attestations, the conceptualization of deity, and the understanding of Iron Age epigraphic Hebrew spellings of the feminine singular suffix, as well as pronominal suffixes. The more complete availability of textual witnesses provides a foundation on which to argue the degree of continuity across more than a thousand years of the appearance of the deity in the West Semitic world.